(3fRhd GdZjK GdPj GfSLe aj TQM dGejI GdYLes - (3eMeO Hf CHj HcQ Hf YeQ Hf CHj HcQ Hf eMeO, GdeNRhej GdbQTj, HOQ GdOjf GdeYQha HGHf GdOeGejfj , J (B827 (3g` s; (3GdUaOj , UdGM GdOjf Ndjd Hf CjHc Hf YHO Gddg GdUaOj, UdGM GdOjf GdUaOj,J (B764 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPj dG jJhLg Ydjg GdEYJQGV aEf HYV ScGf GdEScfOQjI, eef jRYe Cfg ef WdHg GdYde s
(3BNQgG (B:s
(3eY Cfj JQcJ CTjGA de CPcQgG Nha GdEWGdI hGdedd adjbJUQ Ydi gPG GdbOQ aajg caGjI, hGddg GSCd MSf GdNGJeI s
(3fSNI KGfjIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHIs
(3hGdfSNI ebGHdI Ydi fSNI bhHdJ Ydi fSNI GdeDdas
(3hGdNW ajg HYV GdVHW s
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs